Effects of inorganic particles on the crystallization, mechanical properties and cellular structure of foamed PP composites in the IMD/MIM process. Issue 58 (12th November 2021) - Fan, Tao; Zhao, Qianqian; Guo, Wei; Mao, Huajie; He, Bo; Ruan, Wei
Abstract : As the particle size decreased, the relative amount of β-crystal and mechanical properties increased, while the thickness of the core layer gradually decreased. Abstract : Foamed polypropylene (PP) composites containing inorganic particles were prepared using a combined in-mold decoration and microcellular injection molding (IMD/MIM) method, and supercritical fluid-nitrogen was used as the physical blowing agent. Calcium carbonate (CaCO3 ) and montmorillonite (MMT) with particle size that varied from nanometer to micron were selected as reinforcement particles. The effect of inorganic particle type and size on the crystallization, mechanical properties, and cellular structure of the parts were investigated. The results showed that the polymer chains were not well inserted into the MMT layer, and there was almost no increase in the interlayer spacing. As the particle size decreased, the relative amount of β-crystal and mechanical properties increased. The addition of CaCO3 was more effective than MMT at increasing the volume fraction of the β-crystal form when the particle size was reduced to the nanometer level. In the vertical and parallel section, the average cell diameter of the composites decreased and the cell density increased as the particle size decreased. As the particle size of the inorganic filler decreased, the deformation degree of cells gradually increased.